TEKNOLOGI GNSS DALAM MANAJEMEN GEMPA BUMI DI INDONESIA - Agnes Sri Mulyani (UKI Press, 2023)
The high risk of recurring tectonic earthquakes in Indonesia requires regular monitoring. One method that can be used in monitoring earthquakes due to tectonic activity is to observe the position of a monitoring point with GPS. It can provide an overview of the movement of point continuously. GPS is one of the references in geodynamic studies to observe patterns and changes in the direction of movement of blocks of the earth's crust in analyzing active faults in the earth. The position observation method can describe the condition of the monitoring points during one tectonic earthquake phase (earthquake cycle), namely inter-seismic, pre-seismic, co-seismic, and post-seismic. It is necessary to study as early as possible the deformation of tectonic plates so that in the future the risk of damage and loss to the environment due to earthquakes can be minimized. This paper aims to examine GPS technology in monitoring earth dynamics using the literature study method. By inputting GPS data and the output is the fault activity model, it is possible to determine the potential earthquake disaster model in the area studied. It is important to have good and responsive disaster management to minimize the damage caused by a disaster. Areas with a potential for earthquakes must have technology to know if there is an earthquake and where a tsunami will occur, have the infrastructure to transmit this information to residents, and residents must be prepared to know what to do.